KOLABORASI PEMERINTAH DESA MENGATASI PENYALAHGUNAAN NARKOTIKA DI DESA OGOWELE BUGA KABUPATEN TOLITOLI - Mirnawati Mirnawati; Wahyu Perdana Saputra; Arina Silviana; Utari Amanda (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Drug abuse in Indonesia has reached an alarming level, marked by the spread of circulation to rural areas and targeting various levels of society. This condition demands integrated prevention and handling efforts through collaboration between various stakeholders, especially village governments as the front line in community development. Village governments have a strategic role as regulated in Article 26 paragraph (1) of Law Number 6 of 2014 concerning Villages, namely carrying out community development and maintaining social order. This community service activity aims to increase awareness, knowledge, and participation of the people of Ogowele Buga Village, Tolitoli Regency, in efforts to prevent drug abuse through collaboration between the village government, community leaders, and related elements. The methods used in this activity are lectures and interactive discussions, with the delivery of material regarding the types of narcotics, the negative impacts of drug abuse on health, social, and economic, as well as community-based prevention strategies. The results of the activity show an increase in public understanding and awareness regarding the dangers of narcotics and the importance of the active role of village governments and communities in creating a drug-free village environment. This activity is expected to be the first step in strengthening the joint commitment and sustainability of the drug abuse prevention program at the village level.